Prebiotic Maltose Gel Can Promote the Vaginal Microbiota From BV-Related Bacteria Dominant to Lactobacillus in Rhesus Macaque - Zhang, Qiong-qiong; Liu, Zhi-heng; Liu, Li-ling; Hu, Gang; Lei, Guang-lun; Wang, Ying; Cao, Yang; Wu, Wei; Zhang, Lei; Liao, Qin-ping (Frontiers in Microbiology, 2020)
The high incidence of bacterial vaginosis recurrence is common after treatment with an antibiotic agent and suggests the need for new treatments to prevent. We conducted a randomized trial to evaluate the ability of maltose gel to treat bacterial vaginosis. 18 female rhesus macaques were randomly assigned, in a 2:1 ratio, to receive maltose gel or placebo gel by syringe to the fornix of the vagina for five consecutive days. We used 16S RNA sequencing data from 70 swab samples of vaginal secretions in two groups in total. on days 0, 3, and 5 after medication initiation and days 3 and 5 after medication withdrawal for the study of microbiome composition. We found that, in the placebo control group, there was no significant change in the composition and abundance of vaginal microbiota during the follow-up period. In the maltose gel test group, the abundance of Lactobacillus in the vagina microbiota increased gradually with the prolongation of the treatment time on Day 3 and Day 5 (ANOVA p = 6.99e-5 < 0.01), but began to decrease after the withdrawal of maltose gel, which was different from that of the control group. Correspondingly, the diversity and abundance of BV-related bacteria, Fusobacterium, Parvimonas, Mobiluncus, Campylobacter, Prevotella, and Sneathia decreased on Day 0 to Day 5 of medication and increased after drug withdrawal in the maltose gel test group. The study confirms that maltose gel can facilitate the proliferation of Lactobacillus, and promote the transition of the vaginal microbiota from BV-related bacteria dominant to Lactobacillus dominant in the rhesus macaque.